Clinical practice recommendations for hematopoietic cell transplantation and cellular therapies in follicular lymphoma: a collaborative effort on behalf of the American Society for Transplantation and Cellular Therapy and the European Society for Blood and Marrow Transplantation - Iqbal, Madiha; Kumar, Ambuj; Dreger, Peter; Chavez, Julio; Sauter, Craig S.; Sureda, Anna M.; Bachanova, Veronika; Maziarz, Richard T.; Dreyling, Martin; Smith, Sonali M.; Jacobson, Caron; Glass, Bertram; et al. (Transplantation and cellular therapy, 2024)
Follicular lymphoma (FL) is the most common indolent B-cell non-Hodgkin lymphoma (NHL), accounting for nearly one-third of all NHL. The therapeutic landscape for patients with FL has significantly expanded over the past decade, but the disease continues to be considered incurable. Hematopoietic cell transplantation (HCT) is potentially curative in some cases. Recently, the emergence of chimeric antigen receptor T-cell therapy (CAR-T) for patients with relapsed/refractory (R/R) FL has yielded impressive response rates and long-term remissions, but definitive statement on the curative potential of CAR-T is currently not possible due to limited patient numbers and relatively short follow up. A consensus on the contemporary role, optimal timing, and sequencing of HCT (autologous or allogeneic) and cellular therapies in FL is needed. As a result, the American Society of Transplantation and Cellular Therapy (ASTCT) Committee on Practice Guidelines endorsed this effort to formulate consensus recommendations to address this unmet need. The RAND-modified Delphi method was used to generate 15 consensus statements/recommendations. These clinical practice recommendations will help guide clinicians managing patients with FL. Of note, the use of bispecific antibodies in R/R FL was not in the scope of this project.
Online verfügbar: 6. Juli 2024, Artikelversion: 21. August 2024
Gesehen am 12.11.2024